2011
DOI: 10.1371/journal.pbio.1001054
|View full text |Cite
|
Sign up to set email alerts
|

Limbic Justice—Amygdala Involvement in Immediate Rejection in the Ultimatum Game

Abstract: Imaging studies have revealed a putative neural account of emotional bias in decision making. However, it has been difficult in previous studies to identify the causal role of the different sub-regions involved in decision making. The Ultimatum Game (UG) is a game to study the punishment of norm-violating behavior. In a previous influential paper on UG it was suggested that frontal insular cortex has a pivotal role in the rejection response. This view has not been reconciled with a vast literature that attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 38 publications
8
91
4
Order By: Relevance
“…An increased BOLD response could be detected in response to unfair offers in emotion-(anterior insula) and cognition-(dorsolateral prefrontal cortex) related brain regions. Moreover, Gospic et al (2011) could demonstrate that also sub-cortical regions, especially the amygdala, are related to the immediate rejection of unfair offers in the UG. These fMRI findings fit perfectly to the behavioral data and the DRD4 gene effects observed in the present study because DRD4 receptors are dominantly expressed in the brain regions triggering the imaging effects.…”
Section: Discussionmentioning
confidence: 98%
“…An increased BOLD response could be detected in response to unfair offers in emotion-(anterior insula) and cognition-(dorsolateral prefrontal cortex) related brain regions. Moreover, Gospic et al (2011) could demonstrate that also sub-cortical regions, especially the amygdala, are related to the immediate rejection of unfair offers in the UG. These fMRI findings fit perfectly to the behavioral data and the DRD4 gene effects observed in the present study because DRD4 receptors are dominantly expressed in the brain regions triggering the imaging effects.…”
Section: Discussionmentioning
confidence: 98%
“…Results showed a rapid amygdala response to unfair offers that was positively related to aggressive behavior (rejecting unfair offers). Interestingly, administration of a benzodiazepine prior to performing the Ultimatum Game effectively reduced amygdala reactivity to unfair offers, and also decreased rejections of unfair offers (Gospic et al 2011 ) . In line with the study discussed earlier (Mehta and Beer 2010 ) , Gospic and colleagues ( 2011 ) also found that prefrontal regions such as the OFC were activated to support the inhibition of unfair offer rejections, but these prefrontal responses came on line later.…”
Section: Amygdalamentioning
confidence: 99%
“…Across a number of studies that used different methodologies, there is robust evidence that amygdala activity increases in response to emotional signals of social provocation (angry faces) and that this amygdala reactivity is stronger in individuals susceptible to aggressive behavior (e.g., Coccaro et al 2007 ;Beaver et al 2008 ;Lee et al 2008 ;Chan et al 2010 ;Carré et al 2012 ) . These fi ndings suggest that hyper-amygdala reactivity to social provocation may be a neural marker for one's propensity to engage in reactive aggression (see Carré et al 2011 , for review) A recent neuroimaging study more directly linked amygdala function to aggression (Gospic et al 2011 ) . In this study, participants were scanned while playing the Ultimatum Game in the role of responder using procedures similar to the study described earlier (Mehta and Beer 2010 ) , but the design of this newer study was optimized to detect rapid and slower neural responses to unfair offers.…”
Section: Amygdalamentioning
confidence: 99%
“…Note, some of these concerns are ubiquitous in so far as there are biological and, especially, neurological foundations for them. A strong sense of justice, for example, is found in both our primate kin and across all human brains (Gospic et al 2011 )-and, thereby, shapes the microdynamics constraining our everyday experience of social reality (Chap. 18 ).…”
Section: Universal Human Concernsmentioning
confidence: 99%